Rethinking integrated nutrition‐health strategies to address micronutrient deficiencies in children under five in Mozambique. (12th February 2019) - Picolo, Melanie; Barros, Iracema; Joyeux, Mathieu; Gottwalt, Allison; Possolo, Edna; Sigauque, Betuel; Kavle, Justine A.
Abstract: In Mozambique, about two thirds of children 6–59 months of age are affected by vitamin A deficiency and anaemia. The objective of this case study is to provide programme considerations for planning, implementing, monitoring, and evaluating vitamin A and iron deficiency interventions within the context of lessons learned to date for vitamin A supplementation, micronutrient powders (MNPs), and food‐based strategies. For 15 years, the Mozambique Ministry of Health implemented twice‐yearly vitamin A supplementation through both campaigns and routine health services. Yet coverage in 2017 (55%) was not much higher than in 2003 (44%). Reaching every district/reaching every child, a strategy adapted from the field of immunization, was used to achieve equitable coverage of vitamin A and for microplanning of outreach services in health facilities, with support from the Maternal and Child Survival Program. In Mozambique, a free or subsidized distribution model for MNPs has been rolled out, yet integration of MNPs into infant and young child feeding programming (i.e., cooking demonstrations) is needed to reinforce "the who, what, and why" of MNPs through culturally sensitive behaviour change communication. Food‐based strategies to promote dietary diversity, such as through complementary feeding recipes, are also critical. To harmonize efforts, the Mozambique government should consider the development of a national strategy for the prevention and control of micronutrient malnutrition, with clear monitoring and evaluation targets. Ongoing monitoring of the prevalence of micronutrient deficiencies and coverage of implemented micronutrient interventions is needed to make evidence‐based decisions to drive nutrition–health programming.